1989
DOI: 10.1002/pola.1989.080271025
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of polytriazole films: A thermal analysis study

Abstract: SynopsisThe thermal behavior of poly( 1,3-phenyl-l,4-phenyl)-4-phenyl-1,2,4-triazole has been investigated using different scanning calorimetry (DSC) and thermogravimetry (TG). Processes are studied for this thermally stable polymer that take place between 200 and 500°C. While the polycondensation reaction product in powder from appeared to be partially crystalline, films prepared by casting from a formic acid solution appeared to be completely amorphous. A thermal treatment between Tg( -270°C) and T , ( -430'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…A rapid mass loss occurred during the second peak, suggesting thermal decomposition of Na-2-OH-2,6,6-TMBHS. A similar observation of considerable weight loss at the exothermic peak during TGA and DSC for polytriazoles has been reported . Furthermore, the exothermic peak associated with crystallization during TGA and DSC analyses has been discussed in the literature. , Because of probable thermal decomposition, the value of T m for Na-2-OH-2,6,6-TMBHS could not be predicted.…”
Section: Resultssupporting
confidence: 52%
“…A rapid mass loss occurred during the second peak, suggesting thermal decomposition of Na-2-OH-2,6,6-TMBHS. A similar observation of considerable weight loss at the exothermic peak during TGA and DSC for polytriazoles has been reported . Furthermore, the exothermic peak associated with crystallization during TGA and DSC analyses has been discussed in the literature. , Because of probable thermal decomposition, the value of T m for Na-2-OH-2,6,6-TMBHS could not be predicted.…”
Section: Resultssupporting
confidence: 52%
“…DSC thermogram of F3 AmB DMP tips conducted between 0ºC and 180ºC showed a broad endothermic peak at about 160°C. The broad shape and the peak shift from 144°C to 160°C indicated that the reduced crystallinity of the tips and the interaction between the drug and the polymer matrices [85,86]. The increase in temperature during DSC analysis and the relatively small particle size of micronised AmB particles in F3 AmB DMP tips may promote interaction of the AmB crystal with the polymer matrices.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%